2020
DOI: 10.52690/jswse.v1i1.10
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Professional and Pedagogic Competence on Teacher’s Performance

Abstract: The world of education continues to be demanded to be able to produce human resources in accordance with the needs of the community and employment in line with the development of technology and culture of the community. This study examines 1) is there an influence of professional competence on teacher performance; 2) is there any influence of pedagogical competence on teacher performance; and 3) is there an influence of professional competence and pedagogical competence together on teacher performance. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 1 publication
1
28
0
3
Order By: Relevance
“…In addition, they also exhibit exceptional performance in academics. Meanwhile, the present study is partly similar with the study of Murkatik, Harapan and Wardiah (2020) which revealed that professional and pedagogical competence have partially influenced the performance of teachers.…”
Section: Journal Of Socialsupporting
confidence: 87%
“…In addition, they also exhibit exceptional performance in academics. Meanwhile, the present study is partly similar with the study of Murkatik, Harapan and Wardiah (2020) which revealed that professional and pedagogical competence have partially influenced the performance of teachers.…”
Section: Journal Of Socialsupporting
confidence: 87%
“…Research showed that students' learning outcomes were influenced by teacher performance (Suhaimi, Normianti, & Aslamiah, 2019). Teachers are a very dominant element of education in improving the quality of the learning process in schools (Murkatik, Harapan, & Wardiah, 2020). Thus, teacher performance results from work that can obtain in the learning process.…”
Section: Introductionmentioning
confidence: 99%
“…Motivasi mengajar guru merupakan faktor penting dalam meningkatkan kinerja guru dan pendorong kekuatan bagi guru dalam melakukan kegiatan mengajar secara totalitas sesuai ketentuan yang berlaku yang dapat dinilai dari prestasi kerja, pengukuran hasil kerja, peningkatan kerja kinerja, tanggung jawab, sifat pekerjaan, hubungan interpersonal, kemampuan kerja, kehidupan pribadi, kebijaksanaan dan administrasi, kesempatan untuk berkembang, pendapatan dan posisi (Normianti et al, 2019;Sofia & Yulistia, 2020;Surani & Mifthahudin, 2018). Motivasi guru yang tinggi sangat penting karena merupakan salah satu faktor yang memungkinkan mereka untuk secara efisien melaksanakan tugas pendidikan mereka, jika motivasi kerjanya tinggi maka akan berpengaruh tinggi terhadap kinerja dan sebaliknya jika motivasi rendah maka akan menyebabkan kinerja yang dimiliki juga rendah (Engin, 2020;Murkatik et al, 2020). Hal ini didukung oleh penelitian relevan yang menyatakan bahwa kinerja guru dipengaruhi oleh komptensi, motivasi mengajar dan lingkungan belajar (Alhusaini et al, 2020;Mulang, 2021).…”
Section: Pendahuluanunclassified